Syphilitic uveitis: an Asian perspective. Issue 5 (25th April 2008) - Anshu, A; Cheng, C L; Chee, S-P
Abstract : Aim: To examine the clinical manifestations of syphilitic uveitis in a population and review trends in incidence at a tertiary referral centre. Methods: A retrospective, non-comparative interventional case series of 22 consecutive patients with syphilitic uveitis who were managed in the Ocular Inflammation and Immunology Services of the Singapore National Eye Centre between 1995 and 2006. Results: Twenty-two patients (mean age 52.7 years, range 18–78) with a positive serum fluorescent treponemal antibody absorption test (100%) and negative HIV serology were reviewed. Non-granulomatous anterior uveitis was the commonest presenting finding (18/29 eyes, 62.06%). Posterior uveitis was seen in four (13.7%), intermediate uveitis in three (10.3%) and panuveitis was seen in eight (27.5%) eyes at presentation. Vitritis (19 eyes, 65.4%) was the commonest posterior segment finding. The majority (86.4%) had latent syphilis at the time of ocular involvement. An increasing trend in the number of cases of ocular syphilis in the past decade was not observed. Conclusions: Despite resurgence in infectious syphilis, this centre did not see a dramatic rise in cases of syphilitic uveitis. Ocular syphilis presented most frequently as a non-granulomatous inflammation. Therefore, syphilis serology should be sought even for cases of anterior uveitis.